Role of Cholesterol in Formation of Amyloid Plaques in Alzheimer's Disease - Huma Jadur Shruthi (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
Amyloid plaques are one of the key reasons in forforthe progressforion of Alzheimer's Disease the pthe progression(AD), being one of the leading causes of dementia. Recent studies have shown evidence (AD), of the levels of cholesterol playing an important role in the formation of amyloid plaque. This work aims to ofanalyofze the effect of cholesterol levels ananalyzealyzeon increasing amyloid plaqueon accumulation in the brain, how it can influence breakdown of plaqueonthe breakdownamyloid precursor protein (APP),the breakdownplaque and how specific foods and diets(APP),the breakdown can affect thediets(APP), formation of amyloid plaques. The research findings indicate that high levels ofthedietsncelevels of cholesterinfluencelevels ofthey amyloidinfluence enzyme activity and clearance mechanisms in the brain. Low-Density Lipoprotein (LDL), commonly known as 'bad' cholesterol, transports cholesterol to various tissues and has been found to influence the risk of Alzheimer’s disease across different age groups. Managing cholesterol levels before the age of sixty-five may help reduce the likelihood of developing Alzheimer’s.